Management of vulvovaginitis during childhood - Neves, Nilma A. (Brazilian Journal of Sexually Transmitted Diseases, 1998)
Vaginal discharge is a common ailment during childhood and frequently the reason for seeking medical attention. Bad hygiene habits of the extemal genitais, which place unspecified vulvovaginitis as the most frequent cause of vulvovaginitis during childhood, are the cause of the high frequency leveis. When treating the child with vulvovaginitis, it is very important to determine if it is physiological or pathological, thereby avoiding unnecessary treatment. Moreover, it is a known fact that the great majority ofvaginal discharges cease with adequate genital hygiene. ln the cases where the ethiological agent ofvulvovaginitis is considered an agent of STD’s, an investigation to determine if rape occurred should be carried out. The success of the treatment depends on the correct ethiological diagnosis and family counseling. A practical and global management ofvaginal discharge during childhood was outlined and in tbe sarne way, its principal characteristics, diagnosis and treatment were stressed.